Fecal incontinence after obstetric anal sphincter injuries. Issue 1 (8th January 2013) - Huebner, Markus; Gramlich, Nathanja K.; Rothmund, Ralf; Nappi, Luigi; Abele, Harald; Becker, Sven
Abstract: Objective: To determine obstetric variables associated with the long‐term prevalence of flatal and/or fecal incontinence among women who sustained obstetric anal sphincter injuries (OASIS). Methods: In a retrospective study of women who gave birth between January 1974 and December 1983 at the University Women's Hospital, Tuebingen, Germany, women with OASIS (n = 460) were identified on the basis of chart review. Eligible women were recruited to participate in a telephone interview regarding symptoms and their retrospective preference about elective cesarean delivery. Results: The records of 20 999 deliveries, including all modes of delivery, within the 10‐year study period were reviewed, and 99 women who sustained OASIS agreed to participate. The mean follow‐up was 27.5 ± 2.4 years. Among the participants, 39.4% reported fecal or flatal incontinence. Operative vaginal delivery (forceps and/or vacuum) was significantly associated with fecal but not flatal incontinence (odds ratio, 3.27; 95% confidence interval, 1.12–9.56, P = 0.026). Only 9% of women with flatal incontinence and 13% of women with fecal incontinence would have opted retrospectively for cesarean delivery. Conclusion: Operative vaginal delivery was significantly associated with fecal but not flatal incontinence. No other obstetric variables tested were associated with the long‐term prevalence of fecal or flatal incontinence.